Varying rates of patient identity verification when using computerized provider order entry. (7th May 2020) - Fortman, Emilie; Hettinger, A Zachary; Howe, Jessica L; Fong, Allan; Pruitt, Zoe; Miller, Kristen; Ratwani, Raj M
Abstract: Objective: We sought to determine rates of computerized provider order entry (CPOE) patient identity verification and when and where in the ordering process verification occurred. Materials and Methods: Fifty-five physicians from 4 healthcare systems completed simulated patient scenarios using their respective CPOE system (Epic or Cerner). Eye movements were recorded and analyzed. Results: Across all participants patient id was verified significantly more often than not (62.4% vs 37.6%). Vendor A had significantly higher verification rates than not; vendor B had no difference. Participants using vendor A verified information significantly more often before signing the order than after (88.4% vs 11.6%); there was no difference in vendor B. The banner bar was the most frequent verification location. Discussion: Factors such as CPOE design, physician training, and the use of a simulated methodology may be impacting verification rates. Conclusions: Verification rates vary by CPOE product, and this can have patient safety consequences.